Tindakan Hukum Terhadap Kasus Pembalakan Liar di Hutan Riau - Aderiswanto, Rinanda (Universitas Islam Indragiri, 2024)
Indonesia is a country that has a variety of natural preservation, especially its forests, where forests in Indonesia also have a variety of species of both flora and fauna, it is necessary to preserve nature and not damage the sustainability of the forest such as cases of illegal logging. In writing this journal, the author uses library research methods sourced from books, previous journals and newspapers. The formulation of the problem is (1) what is meant by illegal logging, (2) the causes of the difficulty of eradicating the perpetrators of illegal logging in Riau forests, (3) the punishment that can be received for the perpetrators of illegal logging and (4) the efforts of the government and local communities in overcoming the problem of illegal logging. And the conclusions of this paper are (1) illegal logging or illegal logging is an activity or action that involves the exploitation of natural resources in the form of forests without the appropriate government permits, or compliance with environmental regulations where this can cause serious ecological and social impacts, (2) The causes of the difficulty of eradicating illegal logging perpetrators are illegal logging is no longer independent but has been organized so that it has been controlled, the ineffectiveness of laws governing illegal logging, weak coordination between law enforcement officials, sentencing illegal logging perpetrators is often disproportionate or too light so as not to cause a deterrent effect. (3) Criminal law rules for perpetrators of illegal logging have been regulated in article 19 letters A and B jo article 94 paragraph 1 letter a and article 12 letter E jo article 83 paragraph 1 letter B, Law No. 18 of 2013 concerning the prevention and eradication of forest destruction with a maximum prison sentence of 15 years and a maximum fine of Rp. 100 billion. (4) Government efforts in overcoming illegal logging are revitalizing institutions in managing forests, structuring community access to land and forest resources, strengthening the capacity of communities capable of carrying out effective natural resource management and so on. In addition, the community's efforts in helping the government to overcome the problem of illegal logging are that the community must have self-awareness to care and participate in forest management and conservation, provide information if they know of any illegal logging incidents around the forest where they live, carry out reforestation, help monitor the forest, and report if they see illegal logging.